Long-Term Outcome of Microendoscopic Diskectomy for Lumbar Disk Herniation. A Clinical Study of Consecutive 112 Cases with More than 5-Year Follow-Up - Yoshimoto, Mitsunori; Iesato, Noriyuki; Terashima, Yoshinori; Tanimoto, Katsumasa; Takebayashi, Tsuneo; Yamashita, Toshihiko (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2017)
Background Clinical results and recurrence rate after microendoscopic diskectomy (MED) with long-term follow-up is still unclear, in spite of its relatively long history.Materials and Methods A total of 112 who underwent MED participated in this study. Operative time, blood loss, serum C-reactive protein (CRP), creatine kinase (CK), and visual analog scale (VAS) were evaluated as indexes of surgical invasiveness. The 36-Item Short Form Survey Instrument (SF-36), Japanese Orthopaedic Association (JOA) score, patient satisfaction, and recurrence were also evaluated with a follow-up of at least 5 years.Results The mean operative time was 86.7 minutes, and the mean blood loss was 35.7 mL. The mean CRP on postoperative day 3 and CK on the first postoperative day was 0.72 mg/dL and 224.6 IU/L, respectively, and VAS to assess surgical site pain on the first postoperative day was 24.9 mm on average. The improvement rate in the JOA score was 68.7%. The physical component summary of SF-36 in norm-based scoring was improved from 23.4 to 48.6. Overall, 90.8% of patients evaluated their response to the surgery as extremely satisfied or satisfied. The recurrence rate was 10.5%, and reoperation was performed in 7.9% of patients.Conclusions MED is a technique that offers both reduced invasiveness and good long-term clinical results.
Keywords: lumbar disk herniation; microendoscopic diskectomy; long-term clinical results